La préhistoire des basses terres de l’Est de l’Uruguay et du Sud du Brésil - José M. López Mazz (Journal de la Société des Américanistes)
The Atlantic slope of South America was explored and colonised from tenth Millennium before J.C. by hunter gatherers groups. These groups with high mobility are part of an extended sphere of cultural interaction. Later they became less mobile and produced a specific cultural landscape. Their economy was based on products, managed plants and marine resources of the lowlands. From the third millennium before the era these inhabitants acquired some degree of complexity with a strong political system able to withstand social conflict. At the beginning of this period people arrived from Amazonia (Arawak and Guarani). Charrua and Güenoa/Minuan tribes (well known in the sixteenth and seventeenth centuries) were the historical heirs of this long process.